Effect of Common Acids and Anions on the Extraction of Iron (Ii) from Aqueous Solutions into Chloroform Solution Of 4,4´-(1e,1e´)-1,1´-(Ethane-1,2-Diylbis(Azan-1-Yl-1ylidene))Bis(5-Methyl-2-Phenyl-2,3-Dihydro-1h-Pyrazol-3-Ol) - Godwin, Jackson; Inengite, Azibaola Kesieye; Chukwu, Uche John (International Journal of Chemical and Process Engineering Research, 2014)
The effect of common acids, anions, and auxiliary complexing agents in the solvent extraction of Fe2+ from aqueous solutions into chloroform solutions of 4,4´-(1E,1E´)-1,1´-(ethane-1,2-diylbis(azan-1-yl-1ylidene))bis(5-methyl-2-phenyl-2,3-dihydro-1H-pyrazol-3-ol) (H2BuEtP) alone and in the presence of of 1-(3-hydroxy-5-methyl-2-phenyl-2,3-dihydro-1H-pyrazol-4-yl) butan-1-one (HBuP) was studied. Colorimetric method of analysis using 1,10-phenanthroline was used to determine concentrations of Fe2+ in aqueous solutions after extraction and percentage extraction determined by difference. Separation factors βXY were calculated using data from previous studies using same organic phases to determine theoretical conditions for separating Fe2+ from Ni2+, Pb2+, and UO22+. All acids gave > 90% extraction of Fe2+ at most concentrations with HNO3 and H3PO4 giving the highest percentage extraction of 99.93% at 0.01M and 0.1M respectively in the mixed ligands H2BuEtP/HBuP organic system. H3PO4 also gave best extraction of 99.3% at 0.1M in ligand H2BuEtP alone system. Although all anions used for study also gave > 90% extraction of Fe2+ at different concentration in both types of organic phases, CHCOO-, PO43-, Br- and tartrate ions gave the best extraction of Fe2+ with H2BuEtP. Acids and anions behave as salting out agents or masking agents at different concentrations. Calculated separation factors βXY indicated that it was theoretically possible to separate Fe2+ from Ni2+ with H3PO4 only and Fe2+ from Pb2+ with H3PO4, HCl, and EDTA with H2BuEtP alone. With mixed ligands H2BuEtP/HBuP, calculated separation factors βXY showed that it was possible to separate Fe2+ from Ni2+ with HNO3 and H3PO4, Fe2+ from Pb2+ with HCl and oxalate, and Fe2+from U(VI) with CHCOOH, PO43-, Br- and oxalate. The number of batches of extraction n needed to achieve 99.9% separations are also calculated and shown.